2005
DOI: 10.1177/0093854805278416
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Buss-Perry Aggression Questionnaire (BPAQ) With Mentally Ill Male Prisoners

Abstract: Because of the rising frequency and severity of violence in prison populations, quick and accurate screening of aggressiveness is vital. The Buss-Perry Aggression Questionnaire (BPAQ) is a 29-item self-report measure of aggression. Bryant and Smith proposed a refined 12-item, fourfactor version with superior psychometric qualities; however, Williams, Boyd, Cascardi, and Poythress found a different factor structure among jail detainees than is usually found with nonoffenders. The current study used confirmatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 24 publications
6
69
1
2
Order By: Relevance
“…Taken together, the results are clear: The parsimonious models developed by Bryant and Smith (2001) and Diamond et al (2005) not only outperformed all other models, but they also achieved clearly good fit even using stringent criteria on all individual indices and considering the combinational rules of Hu and Bentler (1999). These findings extend past support for these conceptualizations with a different offender population.…”
Section: Phase 1: Model Comparisonsupporting
confidence: 70%
See 2 more Smart Citations
“…Taken together, the results are clear: The parsimonious models developed by Bryant and Smith (2001) and Diamond et al (2005) not only outperformed all other models, but they also achieved clearly good fit even using stringent criteria on all individual indices and considering the combinational rules of Hu and Bentler (1999). These findings extend past support for these conceptualizations with a different offender population.…”
Section: Phase 1: Model Comparisonsupporting
confidence: 70%
“…Of note are the respective R 2 values for Items 3 and 11 as they are the defining difference between the two models. Consistent with Diamond et al (2005), Item 11 had more of its variance explained by the latent construct of anger than did Item 3 used in the Bryant and Smith model.…”
Section: Phase 2: Bryant and Smith Versus Diamond And Colleagues-closmentioning
confidence: 69%
See 1 more Smart Citation
“…The parent instrument, the Buss-Perry Aggression Questionnaire (BPAQ), has been widely used (Buss & Perry, 1992;Buss & Warren, 2000) as a reliable measure of aggression (Archer & Webb, 2006;Buss & Warren, 2000). For purposes of this study, the BPAQ and BPAQ-SF demonstrated acceptable levels of reliability and validity with correctional samples (see Archer & Haigh, 1997a, 1997bDiamond & Magaletta, 2006;Ireland & Archer, 2004;O'Connor, Archer, Hair, & Wu, 2001), including mentally ill prisoners (Diamond, Wang, & Buffington-Vollum, 2005). Cronbach's alpha for the BPAQ-SF was 0.89 for this study population.…”
Section: Methods Participantsmentioning
confidence: 95%
“…To measure self-esteem and aggression, Rosenberg's Self-Esteem Scale (Rosenberg, 1965) (α=.862, 10 items) and The Short-Form Buss-Perry Aggression Questionnaire (α=.882, 12 items) were used, respectively (Diamond et al, 2005). Finally, in terms of game moral positioning, modified scales by Triberti et al were used (Triberti et al, 2015).…”
Section: Methodsmentioning
confidence: 99%